A Deepening Wound in Schools: Adolescents with Divorced Parents and Their Psychological Adjustment - Altın, Merve; Kuyumcu, Behire Elif (Bulletin of Educational Studies, 2024)
The purpose of this study is to examine the psychological adjustment of adolescents students aged 11-18 whose parents are divorced according to various variables. The study was conducted with 199 students whose parents are officially divorced and both parents are alive. Personality Assessment Scale (PAQ) Child Form and Personal Information Form were used as data collection tools in the study. In the analysis of the data: Independent t-test, one-way analysis of variance and correlation tests were used. The results showed that the psychological adjustment of middle school students decreases as the level of education of the mother and father and the number of siblings increase. According to the variables that occur after the divorce, it did not vary according to the frequency of seeing the parent who does not have custody and whether the mother and father married someone else after the divorce. The psychological adjustment of middle school students (except high school) increases as the time passed since the divorce. Among middle school students, the group with the healthiest adjustment is those living with their mothers; the highest psychological adjustment is in those living with their fathers. The positive thoughts of the mother and father about each other supports the psychological adjustment of middle school students (except high school). In middle school students (except high school), the more the father reflects his negative thoughts about his ex-wife to his child, the more unhealthy the adjustment develops. The results obtained were discussed within the framework of the literature.